2005
DOI: 10.1021/ie0503139
|View full text |Cite
|
Sign up to set email alerts
|

Gas−Liquid and Gas−Liquid−Solid Microstructured Reactors:  Contacting Principles and Applications

Abstract: A variety of gas-liquid microchannel reactors have been developed so far, using different contacting principles. Some devices utilize continuous-phase contacting (i.e., nondispersed separate phases with large specific interfaces). Among these are microstructured falling film, overlapping channel, and mesh reactors. Dispersed-phase contacting is obtained when one of the phases is interdispersed into the other phase. Regular flow patterns are provided by the segmented (Taylor) flow in a single microchannel or nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
178
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(179 citation statements)
references
References 86 publications
0
178
0
1
Order By: Relevance
“…In conventional falling film devices, a film with a thickness of 0.5-3 mm is generated. 33 The film flow becomes unstable at high throughput and the film may break up into rivulets, fingers, or a series of droplets at high flow rates. Besides the limitations mentioned in the Table 2, a common drawback of all abovementioned equipment is the inability to condition the drop or film size precisely and to avoid the nonuniformities that arise due to the complex hydrodynamics.…”
Section: Conventional Multiphase Reactorsmentioning
confidence: 99%
“…In conventional falling film devices, a film with a thickness of 0.5-3 mm is generated. 33 The film flow becomes unstable at high throughput and the film may break up into rivulets, fingers, or a series of droplets at high flow rates. Besides the limitations mentioned in the Table 2, a common drawback of all abovementioned equipment is the inability to condition the drop or film size precisely and to avoid the nonuniformities that arise due to the complex hydrodynamics.…”
Section: Conventional Multiphase Reactorsmentioning
confidence: 99%
“…However, instead of considering only classical reactor types one should also examine possible means of process intensification. This can be accomplished by combining reaction and separation in one unit, by designing new reactor configurations or modes of operation, and by miniaturizing the reactor in order to enhance all transport rates (Westerterp, 1992;Jensen, 2001;Hessel et al, 2005). Let us briefly illustrate some of these methods.…”
Section: Process Intensificationmentioning
confidence: 99%
“…Jensen and his coworkers have also shown that, via multichannel integrated design (De Mas et al, 2003;Khan et al, 2004), in principle, scaleup to large production rates is possible even for highly exothermic reactions such as direct fluorination of aromatics. In their comprehensive review paper at CAMURE-5 and ISMR-4 Hessel et al (2005) summarize well the contacting principles in gas-liquid and gas-liquid-solid micro reactors. They review the characteristics of a variety of contacting patterns attempted and report vastly improved mass and heat transfer coefficients, much larger interfacial areas, controllable RTDs, increased volumetric productivity, and ease of scale out.…”
Section: Scaleupmentioning
confidence: 99%
“…As examples one can cite: direct synthesis of hydrogen peroxide (Hessel et al, 2005), direct fluorination (Chambers et al, 2001), photochemical gas-liquid reactions (Ehrich et al, 2002), automated screening of reaction conditions (Churski et al, 2010), fast determination of solubility and diffusivity (Abolhasani et al, 2012;Lefortier et al, 2012), etc. In most cases mass transfer in gas-liquid Taylor flow is a liquid-side controlled process, and authors of papers concerning this problem use the liquid-side volumetric mass transfer coefficient, k L a for characterisation of the mass transfer rate.…”
Section: Introductionmentioning
confidence: 99%